The molecular mechanism of circRHOBTB3 inhibits the proliferation and invasion of epithelial ovarian cancer by serving as the ceRNA of miR-23a-3p - Yihan Fu; Hong Sun (Journal of Ovarian Research, 2022)
Abstract Rising evidences bespeak that circular RNAs are indispensable in regulating cellular biological behaviors and engaging in diseases' occurrence. CircRHOBTB3 has been reported to participate intimately in the progression of some cancers. Nevertheless, the mechanism by which circRHOBTB3 regulates tumorigenesis in epithelial ovarian cancer (EOC) remains ill-defined. The present study determined the expression pattern and bio-effects of circRHOBTB3 in EOC. Furthermore, it revealed that circRHOBTB3 could serve as the ceRNA of miR‑23a-3p to facilitate PTEN expression, suppress proliferation, G1/S transition, invasion, and promote apoptosis in EOC. Summarily, our findings provided a primary research foundation that circRHOBTB3 might be typified as a neoteric biomarker and a promising target of EOC, which is essential for improving the early diagnosis and precision treatment, so as to cut down EOC's mortality finally.